Rho-ROCK liberates sequestered claudin for rapid de novo tight junction formation - Yuma Cho; Akari Taniguchi; Akiharu Kubo; Junichi Ikenouchi (eLife)
The epithelial cell sheet maintains its integrity as a barrier while undergoing turnover of constituent cells. To sustain the barrier continuously, it’s essential to preserve the ‘old’ tight junctions (TJs) between cells being excluded from the sheet and their neighbors while simultaneously forming de novo TJs between newly adjacent cells. However, the molecular mechanisms involved in the formation of de novo TJs remain largely unknown. This study investigates two scenarios: the formation of de novo TJs during the removal of apoptotic cells from mouse monolayer epithelial sheets and during the differentiation of the granular layer in mouse stratified epidermis. We revealed that rapid claudin assembly is achieved by actively regulating the dissociation of the EpCAM/TROP2-claudin complex in both situations. Furthermore, we found that the Rho-ROCK pathway initiates the activation of matriptase, which cleaves EpCAM/TROP2, resulting in the supply of polymerizable claudin from the stockpiled EpCAM/TROP2-claudin complex at the plasma membrane to induce rapid de novo TJ formation.